2005
DOI: 10.1007/s11259-005-3866-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-distance Road Transport on Thyroid and Adrenal Function and Haematocrit Values in Limousin Cattle: Influence of Body Weight Decrease

Abstract: The purpose of this study was to evaluate the effect of long-distance road transport as a relevant stressor on total and free iodothyronines, cortisol levels and haematocrit values in 10 male Limousin cattle. Serum T3,T4,fT3,fT4 and cortisol concentrations were analysed by immunoenzymatic assays. Serum cortisol levels and haematocrit modifications were also evaluated on the basis of percentage body weight decrease. The results showed a general increase of total and free iodothyronines and cortisol levels after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
5
29
0
6
Order By: Relevance
“…Increases in T 3 and T 4 levels after transport confirm that thyroid hormone modifications are an indicator of stress in domestic animals (Fazio and Ferlazzo, 2003;Fazio et al, 2005 and2007) and also show that horse breed, but not age, appears to influence thyroid responsiveness. In fact, the value of thyroid hormone concentrations cannot be used as an absolute value, as it is only useful in terms of its variation when relative basal values are known.…”
Section: Discussionmentioning
confidence: 56%
“…Increases in T 3 and T 4 levels after transport confirm that thyroid hormone modifications are an indicator of stress in domestic animals (Fazio and Ferlazzo, 2003;Fazio et al, 2005 and2007) and also show that horse breed, but not age, appears to influence thyroid responsiveness. In fact, the value of thyroid hormone concentrations cannot be used as an absolute value, as it is only useful in terms of its variation when relative basal values are known.…”
Section: Discussionmentioning
confidence: 56%
“…Активация функции ЩЖ (повышение концентрации Т 4 ) отмечалась после ежедневной одночасовой иммобилизации котов в течение 7 суток [26], мягкого хронического стресса у крыс линий Spraque-Dawley и Wistar (повышение содержания общего Т 4 и Т 3 в сыворотке) [27], длительной транспортировки самцов крупного рогатого скота (увеличение содержания общих и свободных йодтиронинов [28]. Хронический стресс в течение беременности у крыс вызывал разнонаправленные изменения функции ЩЖ: снижение у матери и повышение тиреоидного статуса у потомства [29].…”
Section: влияние многократно повторяющегося и хроническогоunclassified
“…60-Дневный неизбегаемый стресс индуцировал у самцов крыс повышение концентрации Т 3 и снижение Т 4 [22], при хроническом стрессе было отмечено снижение концентрации Т 3 и Т 4 [23]. Содержание животных в условиях неизбегаемого, в отличие от избегаемого стресса [24], воздействие пролонгированного интенсивного стресса [25] явились причиной снижения уровня Т 3 , что показано авторами с использованием морфометрических и биохимических методов анализа.Активация функции ЩЖ (повышение концентрации Т 4 ) отмечалась после ежедневной одночасовой иммобилизации котов в течение 7 суток [26], мягкого хронического стресса у крыс линий Spraque-Dawley и Wistar (повышение содержания общего Т 4 и Т 3 в сыворотке) [27], длительной транспортировки самцов крупного рогатого скота (увеличение содержания общих и свободных йодтиронинов [28]. Хронический стресс в течение беременности у крыс вызывал разнонаправленные изменения функции ЩЖ: снижение у матери и повышение тиреоидного статуса у потомства [29].…”
unclassified
“…En este mismo sentido, Ishiwata et al (2008) no encontraron diferencias en las concentraciones de cortisol en sangre, pre y post transporte, afirmando por tanto que éste no implica una severa situación de estrés en bovinos. Fazio et al (2005) sugieren que las variaciones de cortisol en sangre luego de viajes de corta distancia, dependerían probablemente del contacto que los animales hayan tenido previamente con los operarios.…”
Section: Transporteunclassified
“…Similar results were reported by Ishiwata et al (2008) who did not find differences in plasma cortisol concentration before and after travelling, suggesting that transport had no severe effects on cattle. Fazio et al (2005) suggested that the effects of short-distance road transport on the increase in cortisol levels in cattle, probably depend on preliminary contact with staff during handling. Trunkfield and Broom (1990) reported a sharp response in cortisol levels in calves during the first 2 hours of transport, mainly due to the loading procedure.…”
Section: Physiologymentioning
confidence: 99%